Spin asymmetries in electron-jet production at the future electron ion collider - Zhong-Bo Kang (SpringerOpen, 2021)
Abstract We study all the possible spin asymmetries that can arise in back-to-back electron-jet production, ep → e + jet + X, as well as the associated jet fragmentation process, ep → e+jet(h)+X, in electron-proton collisions. We derive the factorization formalism for these spin asymmetries and perform the corresponding phenomenology for the kinematics relevant to the future electron ion collider. In the case of unpolarized electron-proton scattering, we also give predictions for azimuthal asymmetries for the HERA experiment. This demonstrates that electron-jet production is an outstanding process for probing unpolarized and polarized transverse momentum dependent parton distribution functions and fragmentation functions.